O interrogatório no estado democrático de direito - Formiga, Ulisses de Araújo (2006)
Criminal Procedure enables and regulates the state interference with the individual freedom realm, granting, on the other hand, assurance to people that their rights can only be restricted upon observance of the legal process and as subject to the rights and guarantees provided for in the Constitution. The analysis of the historic evolution of the treatment ascribed to the procedural inquiry enables to verify its legal nature, either as a means of proof or of defense or, further, as both, it reflecting the profile of Criminal Procedure where it is inserted. The elaboration of international treaties influenced the content of the national Constitutions of signatory countries. Brazil incorporated to the Federal Constitution of 1988 a series of individual rights and guarantees, ascribing to Criminal Procedure a clearly guaranteeing nature, determining the issuance of laws for adequacy of Law to the new reality. The modifications implemented in the procedural inquiry ensure to defendant the actual exercise of his right to defense, as regards the Human Being Dignity as a fundament of the Democratic State of Law